A Composition Titled “Sriya Dasami” - I Made Andika Candra Wigraha; I Gede Yudarta; I Gde Made Indra Sadguna (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This study aims to describe and understand the process of creating the Karawitan Sriya Dasami Composition Work, to find out the form and structure of the Karawitan Sriya Dasami Composition Work, to know and understand the value contained in the Karawitan Sriya Dasami Composition Work. The process of creating Sriya Dasami's Karawitan Composition Works is carried out through imaginative and systematic artistic methods, involving six main stages: inspiration, imagination, exploration, formation, refinement, and presentation. This method is rooted in conceptual needs, traditional approaches, contemporary reinterpretations, as well as the empirical experience of creators. The application of this method allows the work to be formed in its entirety with a strong philosophical and musical foundation, and manifested in the form of a presentation based on cosmic symbolism. The creation process is carried out with a musical and visual approach, and utilizes instruments from Gong Kebyar gamelan as a medium of expression. The form and structure of the work are divided into four main sections, which represent the four phases in the astronomical system of the same period. Each piece contains its own musical character with different durations, creating a unique flow dynamic. The main value in this work lies in the efforts of the creator in formulating a new compositional system through the partition of the number ten, as well as the processing of the playing technique that is sourced from the slow but with a contemporary perspective, which reflects the artistic and spiritual identity of the creator.